The effect of using e-money and self-control on student financial management - Sarlina Devi; Yasir Arafat; Maliah Maliah (Journal of Digital Business and Marketing, 2025)
Purpose: This study examines the effect of e-money usage and self-control on the financial management of undergraduate students in the Faculty of Economics and Business at Universitas PGRI Palembang.. Research Methodology: A quantitative approach was employed with a sample of 107 active students selected from a population of 305. Data were collected through questionnaires and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS 25. Results: The findings reveal that e-money usage (t = 2.499, p = 0.014) and self-control (t = 7.610, p = 0.000) each have a significant positive effect on financial management. Simultaneously, both variables explain 57.9% of the variance in students’ financial management (F = 71.370, p < 0.05). Conclusion: Both e-money usage and self-control significantly contribute to students’ ability to manage finances effectively. Self-control plays a stronger role compared to e-money usage in determining financial management behavior. Limitations: The study focuses only on two variables e-money usage and self-control excluding other potential factors such as financial literacy, lifestyle, and socio-economic background. This scope limitation may affect the generalizability of findings. Contribution: This research enriches empirical evidence on the behavioral aspects of financial management among students in the digital payment era and provides practical insights for universities to design programs enhancing students’ self-control and responsible e-money usage.